Sustained minimal residual disease negativity in newly diagnosed multiple myeloma and the impact of daratumumab in MAIA and ALCYONE - San-Miguel, Jesus; Avet-Loiseau, Hervé; Paiva, Bruno; Kumar, Shaji; Dimopoulos, Meletios A.; Facon, Thierry; Mateos, María-Victoria; Touzeau, Cyrille; Jakubowiak, Andrzej; Usmani, Saad Z.; Cook, Gordon; Cavo, Michele; et al. (Blood, 2022)
In patients with transplant-ineligible newly diagnosed multiple myeloma (NDMM), daratumumab reduced the risk of disease progression or death by 44% in MAIA (daratumumab/lenalidomide/dexamethasone [D-Rd]) and 58% in ALCYONE (daratumumab/bortezomib/melphalan/prednisone [D-VMP]). Minimal residual disease (MRD) is a sensitive measure of disease and response to therapy. MRD-negativity status and durability were assessed in MAIA and ALCYONE. MRD assessments using next-generation sequencing (10−5) occurred for patients achieving complete response (CR) or better and after at least CR at 12, 18, 24, and 30 months from the first dose. Progression-free survival (PFS) by MRD status and sustained MRD negativity lasting ≥6 and ≥12 months were analyzed in the intent-to-treat population and among patients achieving at least CR. In MAIA (D-Rd, n = 368; lenalidomide and dexamethasone [Rd], n = 369) and ALCYONE (D-VMP, n = 350; bortezomib/melphalan/prednisone [VMP], n = 356), the median duration of follow-up was 36.4 and 40.1 months, respectively. MRD-negative status and sustained MRD negativity lasting ≥6 and ≥12 months were associated with improved PFS, regardless of treatment group. However, daratumumab-based therapy improved rates of MRD negativity lasting ≥6 months (D-Rd, 14.9% vs Rd, 4.3%; D-VMP, 15.7% vs VMP, 4.5%) and ≥12 months (D-Rd, 10.9% vs Rd, 2.4%; D-VMP, 14.0% vs VMP, 2.8%), both of which translated to improved PFS vs control groups. In a pooled analysis, patients who were MRD negative had improved PFS vs patients who were MRD positive. Patients with NDMM who achieved MRD-negative status or sustained MRD negativity had deep remission and improved clinical outcomes. These trials were registered at www.clinicaltrials.gov as #NCT02252172 (MAIA) and #NCT02195479 (ALCYONE). •In patients with transplant-ineligible NDMM, durable MRD negativity is associated with improved PFS.•Daratumumab-based therapies are associated with higher rates and durability of MRD negativity. [Display omitted]